THE EFFECT OF LEADERSHIP STYLE, MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT MEGA DAYA MOTOR SURABAYA (MAZDA, EAST JAVA BRANCH) - Nitawati, Elly Yuniar; Iman, Nurul; Amanda, Talita (UTSAHA: Journal of Entrepreneurship, 2023)
Managing human resources well is important for an organisation to be able to compete with other more advanced organisations, however, in managing human resources is different from other sources, it requires an effort to establish a harmonious relationship between workers and the organisation. Therefore, the research aims to determine and examine the variables of leadership style, motivation and work discipline that have a simultaneous, partial, and dominant effect on employee performance at PT Mega Daya Motor Surabaya (Mazda, East Java branch). The approach used is a quantitative approach. The data collection used was interviews, questionnaires, and observation. In addition, the sampling technique in this research used probability sampling technique with 60 respondents, employees of PT Mega Daya Motor Surabaya. The results of testing the model simultaneously obtained the value of F count 30.909> F table 2.77. Moreover, the resulting significant value is 0.000 which is < α = 5% = 0.05, so it can be concluded Leadership Style (X1), Motivation (X2) and Work Discipline (X3) simultaneously have a significant effect on Employee Performance (Y) PT Mega Daya Motor Surabaya (Mazda, East Java Branch).